IMPLEMENTASI WORDPRESS CMS UNTUK WEBSITE PROGRAM STUDI TEKNOLOGI INDUSTRI PERTANIAN ITERA DI PROVINSI LAMPUNG SERTA EVALUASINYA MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE - Borneo Satria Pratama; Endo Pebri Dani Putra; Yesta Medya Mahardhika; Nailussa’ada Nailussa’ada (Jurnal Hilirisasi IPTEKS, 2023)
Currently, educational institutions have utilized websites to disseminate information to the academic community and the general public. Therefore, the Agricultural Industrial Technology study program at the Sumatera Institute of Technology (TIP-ITERA) has also taken advantage of technological advancements to develop the study program's website, aiming to fulfill the need to disseminate program-related information. The objective of this initiative was to develop the TIP-ITERA study program's website using WordPress CMS. This activity was conducted at the Agricultural Industrial Technology study program at the Sumatera Institute of Technology, which is located in Lampung Province. The target audience for this activity comprises (1) the TIP-ITERA study program as the main partner, and (2) website visitors, which is consist of the academic community of TIP-ITERA and ITERA, as well as the general public. The outcome of this activity was the development of the website using a Waterfall system development model and a web hosting architecture. Actors involved in the Use Case Diagram for the developed website include administrator and visitors. Furthermore, The website was evaluated using the User Experience Questionnaire (UEQ). The reliability test results analyzed by the UEQ Data Analysis Tool indicated that all data collected for each variable category in the questionnaire were reliable, as the Cronbach Alpha (α) value for all categories was > 0.6. The evaluation results showed that the scores of the developed website in the categories of stimulation, attractiveness, perspicuity, efficiency, dependability, and novelty were 2.293, 2.215, 2.180, 2.130, 2.335, and 1.960, respectively. The overall benchmarking results indicated that all categories in the UEQ were rated as excellent, signifying that the User Experience (UX) performance of the TIP-ITERA study program's website was considered very good.